Nitrogen patterns in subsurface waters of the Yzeron stream: effect of combined sewer overflows and subsurface–surface water mixing - Aucour, A. M.; Bariac, T.; Breil, P.; Namour, P.; Schmitt, L.; Gnouma, R.; Zuddas, P. (Water science and technology, 2013)
Urbanization subjects streams to increased nitrogen loads. Therefore studying nitrogen forms at the interface between urban stream and groundwater is important for water resource management. In this study we report results on water δ18O and nitrogen forms in subsurface waters of a stream (Yzeron, France). The sites studied were located upstream and downstream of combined sewer overflows (CSO) in a rural area and a periurban area, respectively. Water δ18O allowed us to follow the mixing of subsurface water with surface water. Dissolved organic nitrogen and organic carbon of fine sediment increased by 20–30% between rural and periurban subsurface waters in the cold season, under high flow. The highest nitrate levels were observed in rural subsurface waters in the cold season. The lowest nitrate levels were found in periurban subsurface waters in the warm season, under low flow. They corresponded to slow exchange of subsurface waters with channel water. Thus reduced exchange between surface and subsurface waters and organic-matter-rich input seemed to favor nitrate reduction in the downstream, periurban, subsurface waters impacted by CSO.